Utilisation of Game-Based Learning Media to Optimise the Learning Process at Bodhisattva Junior High School Bandar Lampung - Jepisa, Tomi; Herpratiwi, Herpratiwi; Fitriawan, Helmy; Firdaus, Rangga (UNDIKMA, 2024)
Effective and innovative learning is important in improving the quality of education in today's digital era. This study aims to describe the implementation of game-based learning media utilisation in optimising the learning process at Bodhisattva Junior High School in Bandar Lampung. The research method used is the literature review method by analysing 10 journal articles related to the use of game-based learning media. The results showed that the utilisation of game-based learning media at Bodhisattva Junior High School Bandar Lampung proved to be an effective strategy to optimise the learning process. Game-based learning media makes the learning process more interesting and fun, thus increasing students' motivation and engagement in learning. Games allow active interaction with the subject matter and can be tailored to each student's learning ability and pace, enabling more personalised and effective learning..